Quantitative measurement of cerebral blood volume using velocity‐selective pulse trains. Issue 1 (31st October 2016) - Liu, Dexiang; Xu, Feng; Lin, Doris D.; van Zijl, Peter C.M.; Qin, Qin
Abstract : Purpose: To develop a non–contrast‐enhanced MRI method for cerebral blood volume (CBV) mapping using velocity‐selective (VS) pulse trains. Methods: The new pulse sequence applied velocity‐sensitive gradient waveforms in the VS label modules and velocity‐compensated ones in the control scans. Sensitivities to the gradient imperfections (e.g., eddy currents) were evaluated through phantom studies. CBV quantification procedures based on simulated labeling efficiencies for arteriolar, capillary, and venular blood as a function of cutoff velocity (Vc) are presented. Experiments were conducted on healthy volunteers at 3T to examine the effects of unbalanced diffusion weighting, cerebrospinal (CSF) contamination and variation of Vc. Results: Phantom results of the used VS pulse trains demonstrated robustness to eddy currents. The mean CBV values of gray matter and white matter for the experiments using Vc = 3.5 mm/s and velocity‐compensated control with CSF‐nulling were 5.1 ± 0.6 mL/100 g and 2.4 ± 0.2 mL/100 g, respectively, which were 23% and 32% lower than results from the experiment with velocity‐insensitive control, corresponding to 29% and 25% lower in averaged temporal signal‐to‐noise ratio values. Conclusion: A novel technique using VS pulse trains was demonstrated for CBV mapping. The results were both qualitatively and quantitatively close to those from existing methods. Magn Reson Med 77:92–101, 2017. © 2016 International Society for Magnetic Resonance in Medicine